Enfortumab vedotin in metastatic urothelial carcinoma: the solution EVentually? - Maiorano, Brigida Anna; Catalano, Martina; Maiello, Evaristo; Roviello, Giandomenico (Frontiers in Oncology, 2023)
Metastatic urothelial carcinoma (mUC) is an aggressive malignancy with a dismal prognosis. Enfortumab vedotin (EV) is an antibody-drug conjugate consisting of an antibody targeting Nectin-4. This protein is highly expressed in UC cells. After binding, monomethyl auristatin E is released into cells, causing UC cell death. EV has been approved as a single agent for pre-treated mUC, with interesting improvements in response rate and survival in a setting with limited treatment options. More recently, EV approval occurred in cisplatin-ineligible naïve mUC patients in combination with pembrolizumab. Our review aims to summarize the pharmacological properties, clinical studies, and future developments of EV in mUC.